P470 Evolution of asymptomatic unresected lesions in patients operated for multifocal Crohn's disease. (30th January 2023) - Abdalla, S; Lelievre, O; Carbonnel, F; Penna, C; Benoist, S; Brouquet, A
Abstract: Background: Surgery for Crohn's disease (CD) aims to treat symptomatic lesions. In multifocal CD, when surgery is required for a specific symptomatic location, should asymptomatic lesions be resected during the same procedure? Methods: In this retrospective cohort study, all consecutive patients undergoing bowel resection from 2012 to 2021 for multifocal CD and for which CD lesions were not resected (anoperineal disease excluded) were included. Primary endpoint was recurrence on the unresected CD lesions requiring medical treatment intensification or surgery. Univariate analysis of the risk factors for recurrence on the unresected lesions was carried out. Results: Among 318 patients operated for CD, 28 (9%) were included. Median CD evolution duration was 9.5 years. Twenty-five patients (89%) had at least one medical treatment line and 7 (25%) had previous bowel resection for CD. Indication for surgery was complicated CD (stricture, internal fistula) in 24 patients (86%) and CD refractory to medical treatment in 4 patients (14%). Surgery consisted in small bowel resection in 3 patients (11%), ileocolic resection in 13 (46%) and colectomy in 12 (43%). The unresected lesions were located in the small bowel in 7 patients (25%), colon and/or rectum in 12 (43%) and both in the small bowel and colon in 9 patients (32%). At 6 months, clinical improvement was obtained in 18 patients (64%). After un median follow-up of 58.5 months, 13 patients (46%) required treatment step-up, among which 6 (31%) required surgery targeting symptomatic unresected CD lesions refractory to medical treatment. Median progression-free duration was 43.5 months. Risk factors for recurrence on the unresected lesions were associated anoperineal CD (n=8/10, 80% vs n=5/18, 27.8%, p=0.016) and number of preoperative treatment lines≥3 (n=7/8, 87.5% vs n=6/20, 30%, p=0.011). Conclusion: In complicated or refractory multifocal CD, surgery targeting most severe lesions allows clinical improvement in 65% of patients at 6 months. Although nearly half of the patients require medical treatment adaptations for the unresected lesions, only 21% require surgery for these lesions. This strategy combining targeted surgery and medical treatment could be more widely suggested in multifocal CD.